2016
DOI: 10.1016/j.compositesa.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Nano-structured interpenetrating composites with enhanced Young’s modulus and desired Poisson’s ratio

Abstract: This paper has demonstrated that interpenetrating composites could be designed to not only have an significantly enhanced Young's modulus, but also have a Poisson's ratio at a desired value (e.g. positive, or negative, or zero). It is found that when the effect of the Poisson's ratio is absent, the Young's modulus of interpenetrating composites is closer to the Hashin and Shtrikman's upper limit than to their lower limit, and much larger than the simulation and experimentally measured results of the convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In order to enhance the auxetic behaviour (i.e., a large negative Poisson's ratio), a relatively high value of ⁄ is desired. The elastic properties of composites can be significantly affected by the Poisson's ratio of the matrix material [15][16][17], but are less sensitive to that of the reinforcement material (this may be because the volume fraction of the latter is usually much smaller). As almost all the singlephase solid isotropic materials have a positive Poisson's ratio, a very small Poisson's ratio is desired for the matrix material in order to enhance the auxetic behaviour of the composites.…”
Section: Model Parametersmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to enhance the auxetic behaviour (i.e., a large negative Poisson's ratio), a relatively high value of ⁄ is desired. The elastic properties of composites can be significantly affected by the Poisson's ratio of the matrix material [15][16][17], but are less sensitive to that of the reinforcement material (this may be because the volume fraction of the latter is usually much smaller). As almost all the singlephase solid isotropic materials have a positive Poisson's ratio, a very small Poisson's ratio is desired for the matrix material in order to enhance the auxetic behaviour of the composites.…”
Section: Model Parametersmentioning
confidence: 99%
“…With the advance in materials syntheses, experimental measurements and computational simulations, it has been recognised that Poisson's ratio is related to the densification, connectivity, ductility and the toughness of solid materials [14]. It has also been found that the elastic properties of a composite material can be largely affected, thus tuned by the Poisson ratios of the constituent materials [15][16][17]. Cellular materials are often used as filler in sandwich structures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been found that interpenetrating composites reinforced by a self-connected fibre-network have significantly enhanced mechanical properties, such as stiffness and strength, compared to their counterparts with discontinuously reinforced phase structures [6][7][8][9][10][11]. Apart from the improved mechanical properties, good thermal and electrical conductivities [12,13] can also be an advantage for fibre network composites owing to the connected network of fibres.…”
Section: Introductionmentioning
confidence: 99%